Improving Students' Oral Hygiene Through School Dental Health Program: A Meta-Analysis - Wijaya Hermawan, Gandha; Shaluhiyah, Zahroh; Arso, Septo Pawelas (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Oral health is a vital component of overall well-being. The School Dental Health Program (UKGS) is designed to enhance students' oral hygiene through education and health promotion initiatives. This study conducted a systematic review of the literature to evaluate the effectiveness of the UKGS program in improving oral hygiene among students. Subjects and Method: The literature search was conducted in November 2024 using the PubMed, Scopus, and Google Scholar databases. The search employed keywords such as “School Dental Health Program,” “UKGS,” “oral hygiene,” “dental health,” “students,” “school,” “intervention,” “health education,” and “effectiveness.” Studies were included if they evaluated the effectiveness of the UKGS program in improving students' oral hygiene, were published in either Indonesian or English, and utilized quantitative or qualitative research designs. Studies were excluded if they did not address the UKGS program, were not relevant to the research question, used non-empirical methods, or were published before 2010. Due to time constraints, a total of 14 articles were selected for analysis. These studies explored various factors affecting the effectiveness of the program, including the frequency and duration of implementation, educational methods used, support from parents and teachers, and students’ socioeconomic backgrounds. Results: The UKGS program has the potential to enhance students' knowledge, attitudes, and practices related to oral hygiene. However, its effectiveness is influenced by several key factors, including the involvement of parents and teachers, the use of engaging and interactive educational methods, and access to dental health services. Based on these findings, the study offers several recommendations to improve the future effectiveness of the UKGS program. These include increasing the frequency and duration of program implementation, incorporating more interactive and engaging educational approaches, and addressing existing gaps in access to dental health services. Conclusion: The UKGS Program has great potential in improving students' oral hygiene. However, to achieve optimal results, the program needs to be well-designed and consistently implemented by considering various factors that influence its effectiveness. By implementing the recommendations mentioned, it is hoped that the UKGS program can be more successful in improving oral health among students.